Conflict of Laws and Regulations with A Sociology Approach to Law - Hernadi, Henry Sugiharto; Wulansari, Catharina Dewi (Jurnal Hukum Indonesia, 2025)
Legislation which is essentially a set of rules for the Law, which is basically a collection of rules to present an orderly legal and social order, in fact often creates an orderly legal system and society, but in reality often gives rise to conflicts, both internal conflicts between regulations and external conflicts that result in disputes, both between rules and between the government and society. The study of law from the perspective of legal sociology becomes a reasonable scientific instrument. The study of law from the perspective of sociology is a logical tool to dissect the phenomenon of legal problems that occur, this is because in understanding regulatory issues, it is important to see that the upstream and downstream of a regulation is society. Research showed that regulatory issues often arise conflicts in the practice of forming laws and regulations, because in the process of making laws often ignore the procedural due process of law and the substantive due process of law does not consider the correct legal process and the needs of the content of the law, one of the main points is that the widest possible public participation is needed. Where one of the important aspects is the need for community involvement in the rule-making process. As a result, some of the resulting regulations often cause conflicts. As a result, some of the regulations that are made often cause problems due to the incompatibility between the substance of the regulations and the circumstances and needs of the community due to the incompatibility between the content of the regulations and the reality and needs of the community.